A BLAMELESS MIND ‘NOT ON LOAN’ BUT ‘BY NATURE’ (IGNATIUS, TRALL. i. 1) - Schoedel, William R. (The journal of theological studies, 1964)
WILLIAM R. SCHOEDEL; A BLAMELESS MIND ‘NOT ON LOAN’ BUT ‘BY NATURE’ (IGNATIUS, TRALL. i. 1), The Journal of Theological Studies, Volume XV, Issue 2, 1 October 1